Chronic Venous Insufficiency (CVI) - A Study of 100 Cases - Shahin-Ul-Islam, MM; Haque, Md Zahirul; Alam, Saki Md Jakiul; Noman, Mesbahuddin; Siddiqui, FM (Journal of Medicine, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> This study was carried out in the out patient department of Dhaka Medical College Hospital. 100 patients presented with chronic venous insufficiency during the period of January 2005 to June 2005 were studied to find out the various modes of presentation, risk factors and relationship of symptoms with age, sex and Body Mass Index of the patients. It was found that, maximum patients presented with heaviness in the leg (87%), followed by aching leg pain (75%), leg swelling (70%), cramping leg pain (68%), tiredness (48%), burning pain (43%), engorged leg vein (39%), restless leg at night (21%), throbbing leg pain (18%), itching (13%), various skin changes without active ulceration (7%) and active leg ulceration only 3% of cases. Increasing age of the patients, obesity, increasing number of pregnancy, prolonged standing and sitting position at work were found to be positively correlated with CVI. Advanced age is associated with more advanced stage of CVI according to clinical CEAP classification. There is almost equal sex distribution among the stages of CVI except in advanced stage, in stage C4, C5 and C6 there is 10 patients out of them 9 are male and only 1 is female. Relationship of symptoms with BMI of the patients were also sort out and found that, in C3 group of CEAP classification out of 61 patients 46 are obese according to BMI, of which 32 are female and 14 are male and only 17 patients have BMI within normal range, but in other group there is no significant difference in incidence between two groups. Â DOI = 10.3329/jom.v9i1.1421 J MEDICINE 2008; 9 : 20-26